Deficits of Tactile Passive Perception Acuity in Patients With Schizophrenia - Liu, Dan; Fan, Hong Zhen; Zhao, Wen Xuan; Wang, Yun Hui; Li, Dong; Wu, Jing Long; Yan, Tian Yi; Tan, Shu Ping (Frontiers in Psychiatry, 2020)
Background Tactile deficits in schizophrenic patients have rarely been reported. Although cognitive impairments in schizophrenia have been reliably confirmed, the links between tactile deficits and cognitive impairments remain poorly understood. Tactile sensation abnormalities in schizophrenic patients and possible relevant factors need to be investigated. Methods A total of 131 schizophrenic patients (SCZ) and 79 healthy control (HC) participants were included in the study. All subjects were asked to compare the sizes of two consecutive angles from a passive touch using a new developed tactile angle discrimination system aimed at assessing the ability to discriminate tactile angle differences in patients with schizophrenia and healthy controls. The angle discrimination thresholds, representing a person’s tactile perception in the tactile angle discrimination test, were calculated. Results There is a significant group difference in the ability to discriminate tactile angles between the two groups, with angle discrimination thresholds in male patients being significantly higher than in healthy controls (F=8.071,P=0.005), demonstrating that schizophrenic patients have impaired angle recognition from touch stimuli. In addition, patients with schizophrenia had a negative correlation between angle discrimination thresholds and working memory, meaning that the worse their working memory, the worse their tactile angle discrimination capacity. Conclusion To our knowledge, this is the first study to focus on schizophrenic patients who have substantial performance deficits in tactile angle discrimination compared to HC individuals. This finding provides novel evidence of decreased tactile perception in schizophrenic patients, a deficit which can be further integrated into future studies to explore its genetic and neurobiological mechanisms.